Identity of Mequinensa: the «Creation» of Jesús Moncada (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2017)
An overall insight into all of Jesús Moncada’s literary works reveals the clues of what criticism called «the myth of Mequinensa». The research dismantles some of the prefixed ideas on this myth, and considers which aspects involve the particular locus amoenus of the literaturized Mequinensa he created: the description of a specific landscape and the deliberate singularity of its characters, invariably filtered through an ironic lens.Key words: Catalan literature, Jesús Moncada, identity, Mequinensa, irony.